Empirics of Tourism-Led Growth in India, 1995 to 2016 - ROUT, Himanshu B.; MISHRA, P. K.; PRADHAN, B. B. (Journal of Environmental Management and Tourism, 2019)
In the globalized world, the travel and tourism have been considered crucial for achieving inclusive growth, especially in less developed economies. It has been increasingly recognised as a good contributor to national income and employment. So it can be used an instrument for achieving a higher rate of economic growth of a country in the long-run. In this line of argument, this paper examined the causal relationship between tourism and economic growth in the context of Indian States/UTs in a panel data framework. The empirical findings support the tourism-led growth hypothesis in the long-run and growth-led tourism hypothesis in the short-run. Thus, the policy choice is to make the tourism instrumental, through its promotional strategies, for the inclusive and sustainable development of India.